THE ANTIBACTERIAL ACTIVITY OF WATER APPLE LEAVES ACTIVE COMPOUND (Syzygium zeylanicum) AGAINST Escherichia coli AND Staphylococcus aureus - Hamidah, -; Salni, -; Tanzerina, Nina (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
Escherichia coli is one of the bacteria that cause infections in the human digestive tract such as diarrhea, while Staphylococcus aureus is one of the bacteria that cause infections in the skin injury such as boils and pimples. This study used Syzygium zeylanicum leaves because it has potential as a antibacterial because it contains active compounds. This study aimed was determine the antibacterial activity of the fraction and the active compound in Syzygium zeylanicum leaves against Escherichia coli and Staphylococcus aureus. Research conducted on November 2015 to January 2016. The method used in this research were extraction by maceration, fractionation by liquid fractionation, antibacterial activity test, and determination of minimum inhibitory concentration with the diffusion method and isolation of active compounds by column chromatography method. The bacteria used in this test are Escherichia coli and Staphylococcus aureus. Data are presented in tabular form based on the average value of the inhibition diameter and deviation standard. The results of this research showed the water methanol active fraction against the bacteria that used in this test. The methanol water fraction had obtained one antibacterial compound in bottle 1,3,5 which shows the value of tannin Rf 0,416. The minimum inhibitory concentration of water methanol of water apple leaves is 1000 µg/mL for Escherichia coli and 500 µg/mL for Staphylococcus aureus. The minimum inhibitory concentration of the active compound to Escherichia coli and Staphylococcus aureus in 500 µg/mL. The fraction and the active compound of water apple leaves have an antibacterial activity with Escherichia coli and Staphylococcus aureus and the active compound is tannin.